Prenatal diagnosis of terminal 11q deletion - Simão, Laurentino (2011)
The majority of 11q deletion cases described may be included in the “distal 11q deletion syndrome”, or Jacobsen syndrome. This is a rare but clinically recognizable condition with an incidence of 1/ 100,000 births. The most common clinical features are psychomotor delay, characteristic facial dysmorphism and malformations of the heart, kidney, genitalia, central nervous system and skeleton. Patients usually have visible deletions of chromosomal bands 11q23, 11q24, and/or 11q25. Approximately 85% of the cases are de novo deletions, and only a few prenatal cases have been reported. We report the clinical case of a 30-year-old pregnant woman who was referred to our laboratory with a positive first trimester prenatal screening for Down syndrome. The cytogenetic analysis revealed a terminal deletion on the distal 11q chromosome. Fluorescence in situ hybridization using a whole-chromosome painting probe and subtelomeric probes confirmed the terminal deletion and excluded other material involvement. Parental karyotypes were normal. Second trimester ultrasound revealed clinodactyly and a cardiac defect described as a subvalvular and intraventricular communication. The couple opted for medical termination of pregnancy. The postmortem examination of the 22-week fetus showed facial dysmorphism, cardiac defects and uterus bicornis. There are few reports of prenatally diagnosed 11q−,and there seems to be a phenotypic variability. Some cases had a positive prenatal screening for Down syndrome and/or abnormal prenatal ultrasound with olygohydramnios, nuchal thickening, heart malformations and kidney anomalies. Other reports mention no structural fetal abnormalities. The present case, similar to others, had a positive first trimester screening. The fetus presented abnormal fingers, cardiac defects and malformations of genital tract, identified at the second trimester, which is consistent with the del11q− phenotype. This case reinforces the phenotypic variability associated with partial monosomy of distal 11q in the fetus and the difficulty of establishing genotype–phenotype correlations.